Pengaruh Kualitas Pelayanan, Harga, dan Promosi Melalui Media Sosial terhadap Kepuasan Konsumen (Studi Kasus Rumah Makan Jannah Rest Area 260B) (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
This study aims: 1) to determine the effect of service quality on consumer satisfaction at Jannah KM.260b Restaurant, 2) to determine the effect of price on consumer satisfaction at Jannah KM.260b Restaurant, 3) to determine the effect of promotion through social media on consumer satisfaction at Jannah KM.260b Restaurant, 4) to determine the effect of service quality, price and promotion through social media simultaneously on consumer satisfaction at Jannah KM.260b Restaurant. The type of research used in this study is a quantitative approach, this study has a population of 564 with a sample of 85 respondents. Based on the analysis and discussion, it can be concluded where H1: Service quality has a positive and significant effect on consumer satisfaction at Jannah KM.260b Restaurant with a t-count value of 2.066> 1.663 and a significant value of 0.042 <0.05. H2: Price has a positive and significant effect on consumer satisfaction at Jannah KM.260b Restaurant with a t-count value of 2.051 > 1.663 and a significant value of 0.031 < 0.05. H3: Promotion through social media has a positive and significant effect on consumer satisfaction at Jannah KM.260b Restaurant with a t-count value of 5.270 > 1.663 and a sig. value of 0.000 < 0.05. H4: Service quality, price and promotion through social media simultaneously have a positive and significant effect on consumer satisfaction at Jannah KM.260b Restaurant with an F-count value > F-table (20.626 > 2.713) and a significant value of 0.000 < 0.05